1999
DOI: 10.1177/1359104599004002009
|View full text |Cite
|
Sign up to set email alerts
|

A Mental-Health Service for Young People in the Care of the Local Authority

Abstract: Children in care constitute a deprived and needy group of young people, who are at high risk of developing mental-health problems and disorders. This article describes the development of a direct access child and adolescent mental-health service for children living in residential units or with foster families, with data on the pattern and characteristics of referrals, and discussion on the arising difficulties. The main aims of this service are, to be responsive and flexible, to provide mentalhealth assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Children in foster care show an increased prevalence of psychopathology that range from 15 to 57% [6,14,24,30,32,38]. The prevalence rates for children living in residential care are even higher, ranging from 34 to 86% [5,23,27].…”
Section: Introductionmentioning
confidence: 99%
“…Children in foster care show an increased prevalence of psychopathology that range from 15 to 57% [6,14,24,30,32,38]. The prevalence rates for children living in residential care are even higher, ranging from 34 to 86% [5,23,27].…”
Section: Introductionmentioning
confidence: 99%
“…Other professionals that could act on their behalf such as GPs or teachers may be absent at times of placement breakdown and transition (Arcelus, Bellerby & Vostanis 1999). Thus the proportion of LACYP accessing services they need, both specialist and universal, is likely to be lower than among the general population of children and young people.…”
Section: Introductionmentioning
confidence: 99%
“…In a report describing a mental health service for young people in care Arcelus, Bellerby and Vostanis (1999) found that aggressive behavior was one of the main reasons for referral to the service, and Stanley, Riordan and Alaszewski (2005) found that anger and aggression were frequently identified mental health problems. There is evidence that aggression (feelings of anger or antipathy resulting in hostile or violent behavior) and conduct disorders (mental disorders diagnosed due to a repetitive and persistent pattern of antisocial behaviors) in childhood are predictive of aggression in adulthood (Copeland, Miller-Johnson, Keeler, Angold, & Costello, 2007;Loeber & Hay, 1997).…”
Section: Introductionmentioning
confidence: 99%